Soil and plant communities co-regulating plant biomass allocation patterns along a saline-alkali gradient, case study of Allium ramosum in Songnen Grassland, Northeast China - Fu, Changxing; Fan, Jiayan; Fan, Gaohua; Wang, Heqi; Wang, Congwen; Qiang, Wei; Yu, Dafu; Huang, Yingxin (Frontiers in Plant Science, 2025)
AimsPlants have developed sophisticated mechanisms to adapt to changing environments. The strategies for biomass allocation is critical for plant to ensure fitness. Increasing soil salinity has a dramatic impact on plant growth and reproduction from the individual to community level. However, our understanding of how plants adapt their biomass allocation strategies to changes in soil salinity and community structure is incomplete.MethodsWe investigated 122 individuals of perennial herb Allium ramosum from 70 plots along a soil gradient in Songnen grassland. Field investigations determined the physicochemical properties of the soil, aboveground biomass, richness and individual and each organ (root, stem, leaf, flower, and bulb) biomass of A. ramosum.ResultsThe results showed that plant community aboveground biomass and community-weighted height decreased as soil salinity increased. A. ramosum individual size decreased, the allometric exponents between reproductive organs (flowers) and storage organs (bulbs) also decreased, with more biomass allocated to flowers. However, this trend was indirectly influenced by salinization through a reduction in community weighted height (reducing light competition) and community aboveground biomass (altering competitive pressure for resources), rather than a direct response to soil salinity.ConclusionsThis study highlights the complex interplay between community structure and individual plant adaptation strategies in response to environmental gradients, emphasizing the role of community-scale processes in regulating individual resource allocation.